2016
DOI: 10.1016/j.ophtha.2016.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chorioretinopathy Associated with Mitochondrial Trifunctional Protein Disorders

Abstract: Objective To assess long-term effects of genotype on chorioretinopathy severity in subjects with mitochondrial trifunctional protein (MTP) disorders. Design Retrospective case series. Participants Consecutive patients with MTP disorders evaluated at a single center from 1994 to 2015, including 18 subjects with long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD) and 3 subjects with trifunctional protein deficiency (TFPD). Methods Local records from all visits were reviewed. Every subject underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 32 publications
3
30
1
Order By: Relevance
“…Patients with isolated LCHAD deficiency or generalized MTP deficiency share most of the clinical signs and symptoms with other lcFAODs, but are the only lcFAOD in which patients can develop peripheral neuropathy and pigmentary retinopathy [ 23 25 , 62 , 126 128 ]. Even though peripheral neuropathy and pigmentary retinopathy are reported in both LCHAD and MTP deficiency, retinopathy seems to be more prevalent in isolated LCHAD deficiency and peripheral neuropathy is more often seen in MTP deficiency [ 127 130 ]. There is a broad clinical spectrum, but the proportion of patients with a severe clinical presentation and who are refractory to treatment - despite early detection by NBS - is larger than seen in VLCAD deficiency [ 62 , 131 ].…”
Section: Overview Of Different Long-chain Fatty Acid Oxidation Disordmentioning
confidence: 99%
“…Patients with isolated LCHAD deficiency or generalized MTP deficiency share most of the clinical signs and symptoms with other lcFAODs, but are the only lcFAOD in which patients can develop peripheral neuropathy and pigmentary retinopathy [ 23 25 , 62 , 126 128 ]. Even though peripheral neuropathy and pigmentary retinopathy are reported in both LCHAD and MTP deficiency, retinopathy seems to be more prevalent in isolated LCHAD deficiency and peripheral neuropathy is more often seen in MTP deficiency [ 127 130 ]. There is a broad clinical spectrum, but the proportion of patients with a severe clinical presentation and who are refractory to treatment - despite early detection by NBS - is larger than seen in VLCAD deficiency [ 62 , 131 ].…”
Section: Overview Of Different Long-chain Fatty Acid Oxidation Disordmentioning
confidence: 99%
“…Most of these mutations occur at low frequencies. E510Q in TFPα is by far the most common disease mutant, causing long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency and AFLP (5,6,(20)(21)(22)(23). Glu510 is part of the His-Glu catalytic dyad in the active site of HACD (24); and substituting this critical residue by a Gln would abolish HACD activity and jam the β-oxidation cycle at the third step.…”
Section: Implications For Diseases a Plethora Of Mutations In Tfpα Andmentioning
confidence: 99%
“…Ocular damage and poor vision is a unique defect observed in patients with LCHAD deficiency that is not common to other inborn errors of fatty acid oxidation defects. Recent studies have shown that LCHAD-deficient individuals develop retinal dysfunction and chorioretinopathy leading to subnormal vision function [ 48 , 102 , 104 , 105 , 106 ]. The ocular damage is typically accompanied by retinal pigmentation, peripheral neuropathy and cognitive deficiency [ 48 , 103 ].…”
Section: 3-hfa and Pediatric Complications Unique To Lchad Deficiementioning
confidence: 99%